Istidraj As A Metaphor (Study Of Hermeneutic Interpretation) - Afriza, Nugraha Andri; Has, Qois Azizah Bin; Sya'bani, Muhammad Zaky (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This study discusses the sentence sanastadrijuhum in the Qur'an, which is known in society as istidraj. The purpose of this study is to reveal the meaning of istidraj according to the exegetes in a metaphorical and hermeneutic perspective. This study is qualitative and descriptive and uses a literature review method. The data collection technique used is the Mau?u'i method (thematic analysis), while data analysis is carried out using a hermeneutic approach. The main source of this study is the Qur'an al-Karim, with supporting references from various tafsir books that are relevant to the theme. The study results  show that, first, according to the exegetes, sanastadrijuhum is interpreted as a fall that occurs gradually and is almost imperceptible because it happens little by little. Allah SWT provides an opportunity to achieve a high position before being suddenly dropped. Second, metaphorically, istidraj has a satirical meaning, namely the postponement of punishment which is then given at once, both in the context of sin and goodness. Third, from a hermeneutic perspective, istidraj is a form of retribution that occurs through a certain process, either at a fast or slow tempo. This retribution is conveyed through various systematically arranged instruments, such as angels, humans, natural phenomena, or other events that appear natural.